An ERP SAP Implementation Case Study of the South African Small Medium Enterprise Sectors - Aroba, Oluwasegun Julius (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This research examines the enterprise resource planning system (ERP) SAP implementation in SMEs. Small and Medium Enterprises (SMEs) are challenged by their use of manual working style and operations preparations. Human errors in the preparation and execution of important documents such as financial statements, invoices, purchase orders, and internal sales orders have been overcome by business Intelligence processes that computerize every document, efficiently store, Retrieved, and quickly send or receive copies. Methodology – This research proposed solution is an ERP theoretical proposed solution and information evaluation pertinent to the investigation of how to continue and monitor the performance of the ERP SAP procurement process in SMEs. This research technique examines difficulties and suggests solutions. It also includes the stages of the procurement process and the benefit of the enterprise resource planning process, use cases and tables were used to represent the findings generated. Other elements contributing to the ERP procurement process are examined, including the challenges and solutions SMEs face. Furthermore, research on enterprise resource procurement and business intelligence (ERPBI) is conducted to gain in-depth knowledge on how the performance of ERP procurement, including ERP SAP, has been monitored in the existence of SMEs. Findings - ERP implementation and SMEs' outcomes were studied using the explorative approach. To validate the model being created, eight individuals from Business and academia with experience in ERP systems were contacted during the development of the tools. The overall findings offer helpful hints on how organizational and operational elements interact to ensure the successful implementation of ERP. Implementing ERP systems is considered both from the process and organizational learning and knowledge management perspectives. Practical Implications – ERP companies concentrate more on SMEs due to the near-saturation of ERP adoptions in Large Enterprises (LE). Additionally, many SMEs are implementing ERP systems due to globalization, collaboration, value networks, and the massive information flow between and within SAMEs today. Adoption risks stem from SMEs' limited resources and unique qualities that set them apart from Large Enterprises (LE). This article's primary goal is to highlight the aspect of the ERP in the SME domain that needs further research, suggest future research directions, and give the most recent research findings that could help buyers, suppliers, and SMEs when starting ERP projects. More so, there are advantages to implementing an ERP system successfully. However, there is already evidence of substantial failure risks in ERP implementation projects. The non-technical parts of the implementation project are frequently neglected or given less attention by the project managers, who, instead, concentrate primarily on the technical and financial aspects of the project. Therefore, the study of ERP deployment success is one of the key research topics in ERP systems today. Research Limitations – This study contributes to the knowledge of SMEs' ERP intelligence and procurement process implementation.